PROSES KONTRUKSI PEMAHAMAN KONSEP MATEMATIS SISWA MELALUI PENDEKATAN CPA DALAM PEMBELAJARAN MATEMATIKA SD - Hafizhotul Millah, Nabila; Arie Rakhmat Riyadi; Neni Maulida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mathematical concept understanding is the main foundation in learning mathematics, however, its application in elementary schools still faces challenges. This study aims to describe the construction process of mathematical concept understanding through the concrete-pictorial-abstract approach to find students' thinking patterns in constructing the meaning of the concepts learned. A qualitative approach with a descriptive design was used in this study. The subjects of this study were 25 third grade students of SDN Kayuringin Jaya VI Bekasi City. Data were collected through participatory observation and analyzed using Miles and Huberman interactive techniques. The results of this study show that the CPA approach helps students in building conceptual understanding gradually from concrete object manipulation, visual representation, to symbolic understanding. Students not only receive material, but are also actively involved in the exploration of concepts based on direct experience, strengthening their understanding and internalization of the material. Nevertheless, challenges such as the use of manipulative objects at the concrete stage is often considered by students as a mere game remains a major obstacle. In conclusion, learning with the CPA approach has great potential to improve the quality of mathematics learning in elementary schools, especially in building understanding of mathematical concepts gradually and meaningfully, the three stages of CPA help students understand mathematical concepts better.